Information literacy 2.0: hype or discourse refinement? - Špiranec, Sonja; Banek Zorica, Mihaela (2010)
The purpose of this paper is to introduce the term Information Literacy 2.0 as a subset of information literacy, to describe its development and significance and give an outline of its underlying theoretical assumptions. The paper first examines the grounds for the possible re-conceptualizations in the field of information literacy and identifies the current developments in the information universe as the principal drive for perception shifts. Based on a literature review and a descriptive analysis of contrasting features of library user education, information literacy and Information literacy 2.0, the paper highlights the main foci of paradigm shifts. The paper found that the new meaning and understanding of the central conceptions in information literacy are shifting the focus of classical information literacy towards Information literacy 2.0. Many of the aspects of current information literacy practices originate from a print-based culture, which is incongruent with the transient and hybrid nature of digital environments. These radically changing environments are causing the appearance of anomalies in the information literacy paradigm, which could effectively be resolved through the introduction of a sub-concept of information literacy. The article specifies the possibilities for putting theoretical conceptualizations of Information literacy 2.0 into practice by determining the range of shifts in information literacy activities and identifying how new practices differ from the earlier approaches. The study attempts to advance the research field of information literacy by proposing a new outlook on information literacy through the integration of its underlying theoretical conceptions and practical applications.
Projekt MZOS
ENG